Analisis Kebijakan Pidana Penjara Dalam Perspektif Penologi Terhadap Fenomena Overcrowding Lembaga Pemasyarakatan Di Indonesia - Betrilia .; Zalkia Salsabila; Nakayla Azzahwa (GLOBAL SCIENTS PUBLISHER, 2026)
Imprisonment remains the primary instrument in Indonesia’s penal system; however, its dominance has led to the problem of prison overcrowding, which hinders the effective rehabilitation of inmates. This situation highlights a discrepancy between the objectives of punishment from a penological perspective which emphasizes rehabilitation and resocialization and the reality of implementation on the ground. This study aims to analyze prison policies within Indonesia’s criminal justice system and examine their contribution to the phenomenon of prison overcrowding. This study employs a normative legal method using a legislative and conceptual approach, referencing Law No. 1 of 2023 on the Criminal Code, Law No. 22 of 2022 on Corrections, and Law No. 39 of 1999 on Human Rights. The results of the study indicate that although alternative punishments have been established, imprisonment remains dominant, thereby contributing to overcrowding and hindering the achievement of the objectives of punishment. Therefore, the application of alternative punishments must be optimized to reduce reliance on imprisonment.